Reducing Losses from Wind-Related Natural Perils: Research at the IBHS Research Center - Standohar-Alfano, Christine D.; Estes, Heather; Johnston, Tim; Morrison, Murray J.; Brown-Giammanco, Tanya M. (Frontiers in Built Environment, 2017)
The capabilities of the IBHS Research Center full-scale test chamber are described in detail. This research facility allows complete full-scale structures to be tested. Testing at full-scale allows vulnerabilities of structures to be evaluated with fewer assumptions than was previously possible. Testing buildings under realistic elevated wind speeds has the potential to isolate important factors that influence the performance of components, potentially allowing for modifications to standard testing procedures that are commonly used to evaluate product performance. IBHS’s wind-related research is discussed, along with research examining natural perils that are highly affected by wind flows around a structure, such as wind-driven rain during high-wind events and firebrand exposures during wildfires. In addition, IBHS’ hail testing capabilities are described in detail.